Somatometric characteristics of high jumpers - Langer, F. (Acta Universitatis Palackianae Olomucensis. Gymnica, 2007)
The significance of somatic prerequisites for the high jump is evident. In the course of our evaluation, a significant dependence of the physique on performance was confirmed with all the groups of female and male high jumpers having high average performances, which were measured over the period from 1983 to 2005. All these groups were characterized by relatively large homogeneity in most somatic indicators. The measurements we use as a base in the following parts of this paper were carried out over the course of more than two decades. They include single cross-section examinations of the groups of female and male high jumpers (n = 117) as well as longitudinal monitoring of selected individuals. In accordance with the physical development of female and male high jumpers, it is obvious that the groups measured were chosen intentionally and can be designated as "partially selected groups" with respect to both performance and physique. In the course of our examination, changes in the physique, caused by selection and consequently by a specific training load as well as the demanding athletic event itself, can be observed with all the groups.